Total antioxidant activities, phenolic acid and flavonoid content of selected medicinal orchids - Shaari, Norshila (2015)
Orchid family (Orchidaceae) has approximately 20,000 species with more than 850 genera and it is the second largest family of flowering plants. Though orchids are produced primarily as ornamentals, many of them are used as food and herbal medicine. This study determined the total antioxidant activity, phenolic acid content and flavonoid content of different parts of D. crumenatum (stem, leaves and pseudobulb) and A. graminifolia (stem, leaves and root) in three different organic solvents. Methanol, ethanol and distilled water were using as the extraction solvents. Total antioxidant activity was determined by 2, 2 – diphenyl – picrylhydrayl (DPPH) and Ferric reducing antioxidant power (FRAP) methods. In addition, total phenolic acid and flavonoid content were also examined. The result showed that the leaf methanolic extract of D. crumenatum had the highest total antioxidant activity (DPPH and FRAP assay), phenolic acid and flavonoid content with 66.5 mg TE/g DW, 178.82 mg TE/g DW, 8.177 mg GA/g DW and 26.72 mg RU/g DW, respectively. For A. graminifolia, the root methanolic extract exhibited the highest antioxidant activity (DPPH and FRAP assay), phenolic acid and flavonoid content with 31.09 mg TE/g DW, 126.35 mg TE/g DW, 4.95 mg GAE/g DW and 8.56 mg RU/g DW, respectively. The result showed that the correlation between total antioxidant activity with total phenolic acid content and total flavonoid content for both species. These findings support the suggestion that the medicinal orchids may play a role as the base for future drugs and nutrient supplement.